2017
DOI: 10.1016/j.renene.2017.06.084
|View full text |Cite
|
Sign up to set email alerts
|

Distributed control scheme for residential battery energy storage units coupled with PV systems

Abstract: A distributed control method for residential battery energy storage (BES) units coupled with photovoltaic (PV) systems is presented. The objective is to utilize customer owned BES units for solving the over-voltage issues caused by high PV penetration without significantly affecting the BES owners local objectives. 24 hour ahead active power set points of the BES unit are calculated by an optimization based scheduling algorithm. The objective function is locally decided and the optimization is performed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 26 publications
(26 reference statements)
0
30
0
Order By: Relevance
“…The second is that energy arbitrage can be created by shifting energy from valley to peak, based on the different electricity prices between valley and peak hours. An economic analysis of the PV‐BES hybrid system is more complicated than that of the PV system alone because the charge and discharge of the BES is affected by the different behaviours of load energy consumption and PV power generation . The constituents of the total benefit and cost for a PV‐BES system are described in detail as follows: Benefit3=j=italic1N(B3L,j+B3G,j+B3S,j)/1+rj, BL,j3=BPVLitalic3,j+BBitalicPVLitalic3,j+BBitalicgridLitalic3,j, Cost3=CI,italictotal3+j=1N()CitalicOM,j3+CE,j3/1+rj+j'=0{}⌈⌉TPVTB1×TBCR()B,j'3/1+rj'+j''=0{}⌈⌉TPVTinv1×TinvC...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second is that energy arbitrage can be created by shifting energy from valley to peak, based on the different electricity prices between valley and peak hours. An economic analysis of the PV‐BES hybrid system is more complicated than that of the PV system alone because the charge and discharge of the BES is affected by the different behaviours of load energy consumption and PV power generation . The constituents of the total benefit and cost for a PV‐BES system are described in detail as follows: Benefit3=j=italic1N(B3L,j+B3G,j+B3S,j)/1+rj, BL,j3=BPVLitalic3,j+BBitalicPVLitalic3,j+BBitalicgridLitalic3,j, Cost3=CI,italictotal3+j=1N()CitalicOM,j3+CE,j3/1+rj+j'=0{}⌈⌉TPVTB1×TBCR()B,j'3/1+rj'+j''=0{}⌈⌉TPVTinv1×TinvC...…”
Section: Methodsmentioning
confidence: 99%
“…An economic analysis of the PV-BES hybrid system is more complicated than that of the PV system alone because the charge and discharge of the BES is affected by the different behaviours of load energy consumption and PV power generation. 21,22 The constituents of the total benefit and cost for a PV-BES system are described in detail as follows:…”
Section: Cost-benefit Models For a Pv-bes Systemmentioning
confidence: 99%
“…In [27], a coordination mechanism based on a centralized EM structure is used. Mainly, PV battery systems are controlled by independent optimizing local controllers.…”
Section: Coordination Mechanisms For Pv Battery Systemsmentioning
confidence: 99%
“…The authors of [42] suggested that, of the above-mentioned technical challenges, voltage regulation is the most significant technical challenge that prevents or limits the penetration level of the distributed generation in the distribution network, in which the following are the advanced methods or solutions to help mitigate this issue: There has been much research on how these advanced methods can increase the penetration levels of the PV systems in the distribution network [43][44][45][46][47][48][49][50][51][52][53][54][55]. In [43], a new supervisory tool based on the voltage control scheme for control and data acquisition to coordinate among the DGs, OLTC and capacitor banks is presented, which sets a new principle for selecting the tap positions of an OLTC.…”
Section: Technical Solutionsmentioning
confidence: 99%
“…The authors of [54] presented a distributed control method for a residential battery energy storage (BES) units connected to PV system that aims to utilise the customer-owned BES units for solving the over-voltage issues caused by high PV system penetration levels without significantly affecting the owners BES unit local objectives. This method utilises the reactive power when the active power is not enough, and the results show that the aim has been met.…”
Section: Technical Solutionsmentioning
confidence: 99%